The Gods Cities In the Ancient World semantic and toponymic approach. - Haddadou, Yugurtha (Journal of Social Sciences and Humanities, 2023)
The religious thought constituted during antiquity the two worlds of the Mediterraneen and Mesopotamian shores, had impregnated not only daily life but at the same time it shaped the characters and symbolic forms where the cities of the ancient world were constituted.These cities always had rootswhich depended on the nature of the place itself (topographic) and by extention these elements were also reflected throngh its names (onomastic), thus this semitic repertory informs us about this physiognomy under known names like « Gades, Cadis, Bit-El », as well as the temples erected inside these cities like Babel, Ougarit and Byblos.